1986
DOI: 10.1523/jneurosci.06-05-01452.1986
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of the origins of somatostatin-like immunoreactivity in the dentate gyrus of the rat

Abstract: In previous studies, fibers demonstrating somatostatin-like immunoreactivity were observed in the outer half of the molecular layer of the dentate gyrus in the rat and monkey. They occupy the same region as those of the perforant pathway that originates in the entorhinal cortex. Numerous somatostatin immunoreactive neuronal cell bodies were also observed in the hilar region, though stained axonal profiles could not be followed from these cells into the molecular layer. In the present study, several experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(102 citation statements)
references
References 44 publications
8
94
0
Order By: Relevance
“…The excitatory effects of hilar stimulation in these studies were probably due to mossy cells, since mossy cells are the only hilar cells that are known to be immunoreactive for glutamate and project to the contralateral inner molecular layer (Swanson et al, 1978, 198 1;Laurberg and Sorensen, 1981;Bakst et al, 1986;Soriano and Frotscher, in press). Stimulation in control conditions produced inhibitory effects in vivo (Douglas et al, 1983;Bilkey and Goddard, 1987) but weakly excitatory effects after systemic bicuculline (Douglas et al, 1983).…”
Section: Discussionmentioning
confidence: 78%
“…The excitatory effects of hilar stimulation in these studies were probably due to mossy cells, since mossy cells are the only hilar cells that are known to be immunoreactive for glutamate and project to the contralateral inner molecular layer (Swanson et al, 1978, 198 1;Laurberg and Sorensen, 1981;Bakst et al, 1986;Soriano and Frotscher, in press). Stimulation in control conditions produced inhibitory effects in vivo (Douglas et al, 1983;Bilkey and Goddard, 1987) but weakly excitatory effects after systemic bicuculline (Douglas et al, 1983).…”
Section: Discussionmentioning
confidence: 78%
“…Antibodies directed against the peptide somatostatin have revealed that neurons such as the HIPP cells scattered throughout the polymorphic layer are immunoreactive for this peptide, and account for approximately 16% of the GABAergic cells in the dentate gyrus (Morrison et al, 1982;Bakst et al, 1986;Freund and Buzsaki, 1996;Sik et al, 1997;Boyett and Buckmaster, 2001). The somatostatin-positive cells all colocalize with GABA, and are the source of the somatostatin immunoreactive fibers and terminals in the outer two-thirds of the molecular layer.…”
Section: Other Neurons Of the Dentate Gyrusmentioning
confidence: 99%
“…8C), which contains both excitatory mossy cells (Amaral, 1978;Ribak et al, 1985;Soriano and Frotscher, 1994) and a variety of intermingled inhibitory interneurons (Amaral, 1978;Freund and Buzsáki, 1996). To determine whether FG-labeled hilar neurons included a significant number of inhibitory interneurons capable of directly mediating translamellar inhibition, we colocalized FG with GluR2, which primarily labels mossy cells (Leranth et al, 1996), with SS, which labels the largest population of hilar inhibitory interneurons (Bakst et al, 1986;Sloviter and Nilaver, 1987), and with PV, which labels several inhibitory interneuron populations in all dentate subregions (Freund and Buzsáki, 1996;Sloviter et al, 2003).…”
Section: Longitudinal Associational Projections Of Hippocampal Inhibimentioning
confidence: 99%